Avaliação laboratorial e clínica de formulação farmacêutica contendo óleo de Lippia sidoides Cham para o controle de periodontopatias - Gusmão, Isabel Celeste Caires Pereira (2019)
Essential oils have been considered as a promising therapeutic option in periodontal diseases. The objective of this study has been to develop pharmaceutical formulation containing Lippia sidoides Cham oil for control of periodontal diseases. The botanical material (leaves) was collected from the Herbarium of Federal University of Paraíba. The oil was extracted by steam drag and characterized by Nuclear Magnetic Resonance (NMR) and gas chromatography coupled to mass spectrometry (GC-MS). ATCC strains of Aggregatibacter actinomycetecomitans (A. actinomycetecomitans), and Porphyromonas gingivalis (P. gingivalis) were used to evaluate the antimicrobial activity of OELS and the major constituents by broth microdilution technique. The developed pharmaceutical form was orabase paste with two OELS concentrations: 0.15 and 0.25%. Prior to clinical trials, a cytotoxicity experiment and cell damage evaluation by TEM (Transmission Electron Microscopy) and SEM (Scanning Electron Microscopy) biofilm were performed. The phase I clinical trial was developed with 30 participants who used three products: placebo orabase (P, n = 10), orabase with 0.15% OELS (A, n = 10) and orabase with 0.25% OELS. (B, n = 10). The evaluations have been at time zero (TO) before use and after 6 hours of use (T6) and by following techniques: exfoliative cytology with staining, bacterial cell count in saliva and organoleptic tests. NMR and GC-MS have showed that thymol is the major component of OELS. For A. actinomycetemcomitans, the Minimum Inhibitory Concentration (MIC) of OELS, TIM, CAR and CLX was 44.23, 48.25 and 28.45 and 0.042 mg / mL, respectively. For P. gingivalis those values were: 39.30, 28.15 and 28.15 and 0.053 mg / mL. Associations with CLX have indicated synergistic effect. MET images have showed cell wall damage in both microorganisms. OELS concentrations were cytotoxic from 0.15 to 0.25%. The pharmaceutical formulation was stable at room temperature. Preliminary results of 0.15% orabase paste (A) indicate lower antimicrobial effect on T6 when compared to 0.25% paste (B). On the other hand, in T6 paste B resulted in alteration in jugal mucosa cells indicating a possible inflammatory effect. It has concluded that OELS has antimicrobial effect in vitro against periodontal disease related microorganisms and has synergistic effect with CLX. Experiments indicate that OELS has antimicrobial activity in vitro, probably related to the major component (thymol). OELS Orabase Paste has potential for clinical use. The 0.15% OELS orabase paste formulation is safe for short-term intraoral use and has in vivo antimicrobial efficacy. In addition, the observation of synergistic effect of OELS allows us to infer that it is possible to reduce OELS concentrations when in combination with CLX which may potentiate the antimicrobial effect and simultaneously reduce cytotoxicity.